Efficient use of multiculturally cultivated pond fish is a vector for the developmentи of the production of high-quality fish products - L. V. Antipova; E. S. Popov (Новые технологии)
Attracting new raw material sources is based on the existing experience of using fish from the national internal and external water bodies in food, including seas, oceans, rivers, lakes and artificial reservoirs. The purpose of the research is to substantiate the conditions and create high-quality fish products for wide consumer demand based on paddlefish processed product. The object of the research is fresh and chilled American paddlefish grown in polyculture conditions together with silver carp for 2 years, as well as developed fish products produced in laboratory conditions. A generalization of the available information and the results of the research allow us to identify the paddlefish as a highly valuable raw material resource for the production of high-quality fish products. The paddlefish is a technologically advanced fish; it lacks scales, has small costal and intercostal bones and well-developed muscle tissue, and is able to increase the mass rapidly. Paddlefish meat and liver contain all the essential amino acids and biologically active substances. Therefore, these raw materials have significant potential in satisfying physiological needs of the body, and also have high digestibility at the level of 90 and 92%, respectively. The implementation of the developed optimization program has made it possible to create recipe-component solutions for new fish products: meat and fish cutlets, pate and canned food. In the course of determining the quality, nutritional and biological value, technological, consumer and quality advantages of the developed products, created on the basis of raw material combinations of pond fish cutting products grown in polyculture conditions have been established. Modified technological production schemes have been recommended and tested.